Passive UHF RFID Tag for Airport Suitcase Tracking and Identification - Medeiros, C. R.; Costa, J. R.; Fernandes, C. A. (IEEE Antennas and Wireless Propagation Letters, 2011)
A passive UHF tag configuration is presented for suitcase identification and tracking in airport-handling applications. The proposed tag antenna solution is based on a conformal geometry, consisting of a folded dipole with orthogonal arms, appropriate for integration into the wall of injection-molded suitcases during its fabrication process. The tag antenna is designed for the ALIEN Higgs-2 integrated circuit. Simulated frequency dependence of the proposed UHF passive tag shows adequate performance across the world UHF RFID bands. Maximum tag detection range as well as detection isotropy were measured in several test environments both for a prototype tag attached to a suitcase and for a tag embedded in the suitcase wall. Full detection of the embedded tag was obtained for all suitcase orientations in the tested scenarios.